A companion to paleoanthropology - Begun, David R. (Blackwell companions to anthropology, 2013)
"A Companion to Paleoanthropology presents a compendium of readings representing the state-of-the-art in our knowledge relating to the study of ancient humans as found in fossil hominid evidence"--